Aluminium, nitrogen-dual-doped reduced graphene oxide Co-existing with cobalt-encapsulated graphitic carbon nanotube as an activity modulated electrocatalyst for oxygen electrocatalyst for oxygen electrochemistry applications - Kharabe, Geeta Pandurang; Barik, Sidharth; Veeranmaril, Sudheesh Kumar; Nair, Aathira; Illathvalappil, Rajith; Yoyakki, Athira; Joshi, Kavita; Vinod, Chathakudath Prabhakaran; Kurungot, Sreekumar (Small, 2024)
There is a rising need to create high-performing, affordable electrocatalysts in the new field of oxygen electrochemistry. Here, a cost-effective, activity-modulated electrocatalyst with the capacity to trigger both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) in an alkaline environment is presented. The catalyst (Al, Co/N-rGCNT) is made up of aluminium, nitrogen-dual-doped reduced graphene oxide sheets co-existing with cobalt-encapsulated carbon nanotube units. Based on X-ray Absorption Spectroscopy (XAS) studies, it is established that the superior reaction kinetics in Al, Co/N-rGCNT over their bulk counterparts can be attributed to their electronic regulation. The Al, Co/N-rGCNT performs as a versatile bifunctional electrocatalyst for zinc-air battery (ZAB), delivering an open circuit potential approximate to 1.35 V and peak power density of 106.3 mW cm-2, which are comparable to the system based on Pt/C. The Al, Co/N-rGCNT-based system showed a specific capacity of 737 mAh gZn-1 compared to 696 mAh gZn-1 delivered by the system based on Pt/C. The DFT calculations indicate that the adsorption of Co in the presence of Al doping in NGr improves the electronic properties favoring ORR. Thus, the Al, Co/N-rGCNT-based rechargeable ZAB (RZAB) emerges as a highly viable and affordable option for the development of RZAB for practical applications. This manuscript reports the development of a new bifunctional catalyst that exhibits high activity and stability under practical operating conditions. The catalyst (Al, Co/N-rGCNT) is made up of aluminium, nitrogen-dual-doped reduced graphene oxide sheets co-existing with the in situ formed cobalt-encapsulated CNT units is synthesized by a scalable pyrolysis method in an inert Ar atmosphere. The developed electrocatalyst achieved enhanced the oxygen reduction reaction (ORR) and the oxygen evolution reaction OER activity as a result of the favorable synergistic modulations and the system can serve as a process-friendly air-electrode for rechargeable zinc-air battery (RZAB). image
Keywords: Al; Bifunctional catalyst; DFT study; encapsulated structure; N-dual doping; Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable zinc-air battery; X-ray absorption spectroscopy

Aldol Condensation of Furfural with Acetone by Using Mg-Al-O-t-Bu HT Catalyst and Kinetic Studies - Patil, Sneha; Kamble, Paresh; Vinod, Chathakudath Prabhakaran; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Industrial & Engineering Chemistry Research, 2025)
An environment-friendly method for producing jet fuel precursors involves the aldol condensation of biomass-derived chemicals. In this study, the condensation reaction between furfural and acetone was performed using a Mg-Al-O-t-Bu hydrotalcite (HT) catalyst, achieving a furfural conversion of 99% and a selectivity of 82% toward 4-(2-furyl)-3-buten-2-one (FAc). The kinetics of the process were evaluated using a Langmuir-Hinshelwood-Hougen-Watson (LHHW) model across a range of temperatures, and the model showed an excellent fit to the experimental data. The effect of different catalysts, reaction temperatures, catalyst loadings, molar ratios, and reaction times was systematically investigated. The Mg-Al-O-t-Bu HT catalyst was extensively analyzed through techniques such as XRD, XPS, FTIR, nitrogen adsorption-desorption measurements, and CO2-TPD. The catalyst exhibited excellent stability, maintaining its performance consistently across five successive reaction cycles with no notable decline in activity. These findings highlight the industrial relevance of Mg-Al-O-t-Bu HT as a robust and recyclable solid base catalyst for biomass upgrading, with strong potential for process scale-up in renewable fuel production.